2005
DOI: 10.1073/pnas.0504954102
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the streptococcal cell wall C5a peptidase

Abstract: The structure of a cell surface enzyme from a Gram-positive pathogen has been determined to 2-Å resolution. Gram-positive pathogens have a thick cell wall to which proteins and carbohydrate are covalently attached. Streptococcal C5a peptidase (SCP), is a highly specific protease and adhesin͞invasin. Structural analysis of a 949-residue fragment of the [D130A,S512A] mutant of SCP from group B Streptococcus (S. agalactiae, SCPB) revealed SCPB is composed of five distinct domains. The N-terminal subtilisin-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 37 publications
0
69
0
Order By: Relevance
“…Because of the limited sequence identity of SpyCEP with existing structural models (the C5a peptidases from S. pyogenes and S. agalactiae; Brown et al, 2005), we proceeded with attempts to crystallize selenomethionine derivatives of SpyCEP, which contains 29 methionines. After multiple screens using SpyCEP 245-1131245- , SpyCEP 113-1131 , the SpyCEP 113-244 -SpyCEP 245-1131 complex and SpyCEP 34-1613 samples, crystals suitable for X-ray diffraction were obtained only for the SpyCEP 34-1613 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the limited sequence identity of SpyCEP with existing structural models (the C5a peptidases from S. pyogenes and S. agalactiae; Brown et al, 2005), we proceeded with attempts to crystallize selenomethionine derivatives of SpyCEP, which contains 29 methionines. After multiple screens using SpyCEP 245-1131245- , SpyCEP 113-1131 , the SpyCEP 113-244 -SpyCEP 245-1131 complex and SpyCEP 34-1613 samples, crystals suitable for X-ray diffraction were obtained only for the SpyCEP 34-1613 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ACP, a virulence factor and prototype for the Alp family of proteins, is the first surface protein identified to bind integral host cell-surface receptors, GAGs and a 1 b 1 -integrin. Structural analysis of the GBS C5a peptidase (SCPB) suggests that it too may bind integrins via the RGD motif (Brown et al, 2005), but this has not been demonstrated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies of b 2 -integrin may reveal its possible relation to GBS disease. Structural analysis of SCPB suggests that it binds integrin via one or more RGD motifs (Brown et al, 2005), which would give GBS the ability to bind other integrin heterodimers and possibly activate multiple signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ScpB, which is a GBS cellsurface protein previously characterised for its ability to cleave the complement-derived chemoattractant C5a (Beckmann et al, 2002), can bind fibronectin (Cheng et al, 2002). ScpB can bind to integrins, which may promote both binding to host cells and complement proteolysis (Brown et al, 2005). Naturally occurring ScpB variants with a deletion that destroys peptidase function retain the capacity to bind fibronectin (Cleary et al, 2004, Tamura et al, 2006.…”
Section: How Does Gbs Colonize the Urogenital Tract?mentioning
confidence: 99%